Unusual solute segregation phenomenon in coherent twin boundaries - He, Cong; Li, Zhiqiao; Chen, Houwen; Wilson, Nick; Nie, Jian-Feng (Nature communications, 2021)
Interface segregation of solute atoms has a profound effect on properties of engineering alloys. The occurrence of solute segregation in coherent twin boundaries (CTBs) in Mg alloys is commonly considered to be induced by atomic size effect where solute atoms larger than Mg take extension sites and those smaller ones take compression sites in CTBs. Here we report an unusual solute segregation phenomenon in a group of Mg alloys—solute atoms larger than Mg unexpectedly segregate to compression sites of {10 1 ¯ 1} fully coherent twin boundary and do not segregate to the extension or compression site of {10 1 ¯ 2} fully coherent twin boundary. We propose that such segregation is dominated by chemical bonding (coordination and solute electronic configuration) rather than elastic strain minimization. We further demonstrate that the chemical bonding factor can also predict the solute segregation phenomena reported previously. Our findings advance the atomic-level understanding of the role of electronic structure in solute segregation in fully coherent twin boundaries, and more broadly grain boundaries, in Mg alloys. They are likely to provide insights into interface boundaries in other metals and alloys of different structures. Segregation of solute atoms at interfaces affects the properties of alloys and needs to be understood to allow their rational design. Here the authors report an unusual solute segregation phenomenon in a group of Mg alloys, driven by chemical bonding, where solute atoms larger than Mg segregate to compression sites of specific fully coherent twin boundary.